Entrepreneurial spirit and self-efficacy askey factors for technology entrepreneur new venture creation - Abdullah, Sahadah; Rahim, Mohd Syahrir; Zainol, Asif Zamri (2013)
Technology entrepreneur new venture creation (TENVC) plays an important role in developing and commercializing technologies worldwide.Yet, one of the critical and on-going debates is between the paradigm shifts from trait approach to the behavioral approach which emerge from what successful entrepreneurs do and how they perform, rather than what their personality traits. Therefore, the purpose of this research is to study both entrepreneurial spirit and self-efficacy as key factors for TENVC.Mixed methods research was employed combining quantitative and qualitative approach.The samples were chosen based on convenience sampling for quantitative study and judgment sampling for qualitative study.The finding shows that both entrepreneurial spirit and self-efficacy are correspondingly important for TENVC among technical students and IHLs.There is only small different value of their positive significant relationship lead by self-efficacy compared to entrepreneurial spirit with r=.005 and r=.004 for both TENVC of technical students and current status of TENVC in IHLs.This finding is convergent with the outcome from the case study analysis that both factors are among the key indicators for TENVC of technical student and the current status of TENVC in IHLs.The technology entrepreneur development organizations (TEDO) may utilize this result in developing TENVC in their institution.